Role of Corporate Social Responsibility in Supply Chain Management and Increasing Corporate Value - Yuesti, Anik; Ayu R. Rumanti, I Gusti; Kepramareni, Putu; Suardhika, I Nengah (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to determine the effect of profitability, leverage and company size on firm value as well as the role of corporate social responsibility (CSR) in supply chain management, moderating the effect of profitability, leverage and company size on firm value. The sample comprises 28 manufacturing companies listed on the Indonesia Stock Exchange, taking their financial reports from 2015 to 2017. Data were collected from the annual financial statements of the companies obtained from the IDX. Data were analysed through classic assumption test, interaction test with moderated regression analysis and F and t test for significance. Results showed that profitability positively and significantly affects 4,679 firm value with a significance level of 0,000. Leverage negatively and significantly affects -2.682 firm value with a significance level of 0.009. The size of the company positively and significantly affects 3,851 company value with a significance level of 0,000. Interaction analysis results show that CSR moderates the effects of profitability, leverage and company size on firm value.